Management of Organic Waste - Kumar, Sunil; Bharti, Ajay (IntechOpen, 2012)
This book reports research on the utilization of organic waste through composting and vermicomposting, biogas production, recovery of waste materials, and the chemistry involved in the processing of organic waste under various processing aspects. A few chapters on collection systems and disposal of wastes have also been included.